POLA HUBUNGAN POLITIK DAN HUKUM DALAM KEBIJAKAN PERPINDAHAN IBU KOTA NEGARA KE KALIMANTAN TIMUR - Irhammudin; M. Iqbal; Dedi Setiawan; Reza Praditya Pradana (Journal Evidence Of Law, 2022)
All countries need a system of government to regulate the wheels of government. Indonesia as a democratic country that adheres to a presidential system, applies the Trias Politica concept as an effort to separate power into three branches, namely executive, legislative and judicial. The 1945 Constitution implicitly supports this concept by explaining each task and authority of the branch of power in different articles. The duties and authorities of the President as an executive body are regulated in Article 4 paragraph 1, Article 5 paragraph 2, and Article 20 paragraph 4. The DPR as a legislative body is clearly regulated in Articles 19 to 22. While the Supreme Court and the Constitutional Court as judicial branches are regulated in Article 24. This paper tries to unravel the pattern of political and legal relations in the policy of moving the State Capital from DKI Jakarta Province to East Kalimantan Province. The President as the executor of the Act certainly needs support from the DPR as the legislator in order to realize the implementation of the transfer of the new state capital. This is important because the stipulation and implementation of laws is supervised by the Supreme Court and the Constitutional Court as judicial institutions. The hope is that the administration of government can run according to the laws and regulations and the stability of the country is maintained This is important because the stipulation and implementation of laws is supervised by the Supreme Court and the Constitutional Court as judicial institutions. The hope is that the administration of government can run according to the laws and regulations and the stability of the country is maintained This is important because the stipulation and implementation of laws is supervised by the Supreme Court and the Constitutional Court as judicial institutions. The hope is that the administration of government can run according to the laws and regulations and the stability of the country is maintained.